Mechanism of parkinsonian neuronal oscillations in the primate basal ganglia: some considerations based on our recent work - Nambu, Atsushi; Tachibana, Yoshihisa (Frontiers in Systems Neuroscience, 2014)
Accumulating evidence suggests that abnormal neuronal oscillations in the basal ganglia contribute to the manifestation of parkinsonian symptoms. In this article, we would like to summarize our recent work on the mechanism underlying abnormal oscillations in the parkinsonian state and discuss its significance in pathophysiology of Parkinson’s disease. We recorded neuronal activity in the basal ganglia of parkinsonian monkeys treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine. Systemic administration of L-DOPA alleviated parkinsonian motor signs and decreased abnormal neuronal oscillations (8-15 Hz) in the internal (GPi) and external (GPe) segments of the globus pallidus and the subthalamic nucleus (STN). Inactivation of the STN by muscimol (GABAA receptor agonist) injection also ameliorated parkinsonian signs and suppressed GPi oscillations. Blockade of glutamatergic inputs to the STN by local microinjection of a mixture of 3-(2-carboxypiperazin-4-yl)-propyl-1-phosphonic acid (glutamatergic NMDA receptor antagonist) and 1,2,3,4-tetrahydro-6-nitro-2,3- dioxo-benzo[f]quinoxaline-7-sulfonamide (glutamatergic AMPA/kainate receptor antagonist) suppressed neuronal oscillations in the STN. The STN oscillations were further attenuated by the blockade of GABAergic neurotransmission from the GPe to the STN by muscimol inactivation of the GPe. These results suggest that cortical glutamatergic inputs to the STN and reciprocal GPe-STN interconnections are both important for the generation and amplification of the oscillatory activity of GPe and STN neurons in the dopamine-depleted state. The oscillatory activity in the STN is subsequently transmitted to the GPi and may contribute to manifestation of parkinsonian symptoms.